Оптимізація психологічного вивчення персоналу поліції ювенальної превенції з метою здійснення професійного добору і призначення осіб на посади - Барко, В. І.; Barko, V. I.; Євдокімова, О. О.; Yevdokimova, O. O.; Остапович, І. П.; Ostapovych, I. P.; Olena Yevdokimova (Вісник Харківського національного університету внутрішніх справ. – 2025. – № 1 (108), ч. 1. - С. 467-483, 2025)
Статтю присвячено проблемі пошуку оптимального психодіагностичного інструментарію, за допомогою якого психологи отримують можливість комплексного вивчення індивідуально-особистісних властивостей (характеристик) поліцейських з метою їх психологічного добору на службу і призначення на посади. Проведено емпіричне дослідження з охопленням репрезентативної вибірки працівників поліції підрозділів ювенальної превенції, яке ґрунтується на теоретичній концепції, в основу якої покладено принципи системності, оптимізації, теорії інтегральної індивідуальності, рис і ортогональних моделей. На цій основі розроблено оригінальний психодіагностичний комплекс методик для системного психодіагностичного дослідження особистості, який включає адаптовані тести загальних здібностей, індивідуально-особистісних характеристик і спрямованості. Показано, що цей комплекс дозволяє психологу порівнювати, уточнювати й доповнювати отримані при тестуванні результати і формулювати надійний психодіагностичний висновок.

The article is devoted to the problem of finding the optimal psychodiagnostic tools that would enable a comprehensive study of individual and personal characteristics of police officers with a view to their psychological selection for service and appointment of current police officers to positions. An empirical study has been conducted covering a representative sample of police officers of juvenile prevention units, based on the theoretical concept of studying the individuality of a police officer based on the principles of systematicity, optimization, theories of integral individuality, traits and orthogonal personality models; the use of scientifically based criteria and indicators of a person’s psychological suitability for police work, which reflect the main individual and personal characteristics of police officers, as well as the implementation of the original author’s psychodiagnostic complex of valid and reliable methods of systematic psychodiagnostic research of police officers. A variant of the diagnostic complex is proposed, which includes adapted tests: general abilities (Amthauer’s level and structure of intelligence, Manoilova’s emotional intelligence, Mede-Piorkowski’s creativity); individual and personal characteristics (questionnaires of Individual-Typological, Mini-Multiple and Big Five), orientation (questionnaires of Richie-Martin and Jones-Crendall). The fact that subjective questionnaires belong to the theoretical orthogonal individual-personality model allows the psychologist to compare, clarify, and supplement the results obtained during testing and formulate a reliable psychodiagnostic conclusion. Thus, according to most criteria and relevant indicators, the psychodiagnostic tools selected for predicting the success of juvenile prevention police officers work successfully. The study using this complex confirmed the possibility of successful differentiation of juvenile prevention police units by levels of psychological fitness for duty and thus predicting the success of their professional actions as police officers.
Optimisation of psychological assessment of juvenile prevention police personnel for the purpose of professional selection and appointment
Keywords: психологічне вивчення; поліція ювенальної превенції; психодіагностика; професійний добір; загальні здібності; індивідуально-особистісні властивості (характеристики); psychological study; juvenile prevention police; psychodiagnostics; professional selection; general abilities; individual and personal properties